THE EFFECT OF USING SELF-EXPLANATION READING TRAINING (SERT) STRATEGY ON STUDENTS’ READING COMPREHENSION - roswati roswati; fauzan ahmad (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
The aim of this study was to analyze the effect of using self-explanation reading training (sert) strategy on students’ reading comprehension. This research applied a Quasi-experimental research. There were 44 students as sample from 153 students of eleventh grade at MA Darul Hikmah Pekanbaru by using cluster random sampling technique. This researcher used multiple choice test. T-test was used to analyze the data. This research used an independent t-test formula by using SPSS 16 version. Based on the analysis of T-test Formula, Ha is accepted because the sig. value is 0.000<0.05. The research was conclude that there is significant difference of using Self-Explanation Reading Training (SERT) Strategy on reading comprehension in report text of the eleventh grade students at MA Darul Hikmah Pekanbaru.